Using natural capital and ecosystem services to facilitate participatory environmental decision making: Results from a systematic map - Caitlin Hinson; Jimmy O’Keeffe; Ana Mijic; John Bryden; Jessica Van Grootveld; Alexandra M. Collins (People and Nature, 2022)
Abstract The rights all people have for involvement in environmental decision making has long been established yet collaborative resource management has had mixed success. Natural capital; the renewable and non‐renewable natural assets that benefit societies, and the flow of ecosystem services these assets provide, are increasingly promoted as approaches that ensure consideration of the environment in decision making. Natural capital and ecosystem services concepts can facilitate participation in decision making by explicitly describing the role of the environment in sustaining society. Increased promotion of these approaches requires consideration on how best to involve stakeholders, those involved and affected by a decision, in the process. We conducted a systematic search to identify where stakeholders have participated in natural capital, ecosystem services and nature’s contributions to people decision making, creating a systematic map of 56 case studies. While many papers discussing stakeholders and these concepts were found, few actively engaged stakeholders in a decision‐making process that used the concepts and therefore were included in the map. Where stakeholders were involved, engagement methods included focus group discussion, stakeholder negotiation and scenario development, as well as ecosystem service ranking and mapping. Ranking for prioritisation of ecosystem services was common, with a bias towards using services with a direct tangible economic benefit; food production and tourism, are both prominent examples. A limited number of case studies performed robust participatory methods evaluations, offering little indication of how best to use natural capital or ecosystem services in participatory approaches. Therefore, the work highlights need for greater evaluation of participatory processes involving natural capital to ensure stakeholder engagement is efficient, productive and useful to all involved. Read the free Plain Language Summary for this article on the Journal blog.